COMBINATION OF FOOT EXERCISE AND DIABETES EXERCISE ON ANKLE BRACHIAL INDEX IN DIABETIC PATIENTS - Muthmainnah; olsi Rahmi, Yuza; Nur Achriyana Arif, Rifda; Astilia; Islamiyah, Tsuwaibatul (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2025)
Abstrack Background: Diabetes mellitus has a negative impact on both the psychological and physical well-being of patients. Most amputations experienced by DM patients can be prevented by performing foot care and engaging in physical exercises such as diabetic gymnastics and foot exercises. Aim: to identify the influence of diabetic exercise and foot exercise on ABI in type 2 DM patients. Method: This quasi-experimental study with a one group pre-test-post-test design involved 36 respondents divided into two groups. The research sample was recruited through consecutive sampling at the Endocrinology Clinic of RSUP Dr. Hasan Sadikin Bandung. The intervention group was given diabetic exercises and foot exercises 3 times a week for 45 minutes over 4 weeks. ABI measurements were taken using a sphygmomanometer and Doppler. Results: Data were analyzed using the Mann-Whitney test. The research results show a significant difference in blood glucose levels between the intervention group (p<0.05). Conclusion: This study recommends that type 2 DM patients are expected to utilize diabetic foot exercises as a natural exercise for the prevention of complications in type 2 DM patients, particularly in the foot area.